Wireless Medical Sensor Networks for IoT-based eHealth - Al-Turjman, Fadi (The Institution of Engineering and Technology, 2020)
The Internet of Things (IoT) is enabling several applications/services in healthcare and medical fields. Due to the rapid proliferation of wearable devices and smartphones, the IoT-enabled technology is evolving healthcare from conventional hub-based system to more personalized eHealth systems. The successful utilization of IoT-enabled technology in eHealth will enable faster and safer preventive care, lower overall cost, improved patient-centric practice, and enhanced sustainability. Efficient IoT-enabled eHealth systems can be realized by providing highly customized access to rich medical information and efficient clinical decisions to each individual with unobtrusive monitoring. Wireless medical sensor networks (WMSNs) are at the heart of this concept, and their development is a key issue if such concept is to achieve its potential. This book addresses major challenges in realizing WMSNs in the forthcoming IoT-based eHealth systems. Challenges vary from cost and energy efficiency to security and service quality. To tackle such challenges, WMSNs must meet certain expectations and requirements, such as size constraints, manufacturing costs, resistance to environmental factors existing at deployment locations, etc. Based on that, the aim of this book is to focus on both design and implementation aspects in IoT-based eHealth applications that are enabled/supported by WMSNs in realizing patientcentric systems.
Keywords: Medical informatics.; Wireless sensor networks.; Internet of things.; elektronické knihy; electronic books